Blue rings in trees and shrubs as indicators of early and late summer cooling events at the northern treeline - Buchwal, Agata; Matulewski, Pawel; Sjöberg, Ylva; Piermattei, Alma; Crivellaro, Alan; Balzano, Angela; Merela, Maks; Krže, Luka; Čufar, Katarina; Kirdyanov, Alexander V.; Bebchuk, Tatiana; Arosio, Tito; et al. (Frontiers in Plant Science, 2025)
The high temperature sensitivity of pine trees in northern Fennoscandia has led to some of the most reliable tree-ring climate reconstructions in the world for the past millennia. However, wood anatomical anomalies that likely reflect temperature-induced reductions in cell wall lignification, the so-called Blue Rings (BRs), have not yet been systematically investigated in trees and shrubs in northern Europe. Here, we present frontier research on the occurrence of BRs in Pinus sylvestris trees and Juniperus communis (L.) s.l. shrubs from the upper treeline in northern Norway (69°N) in relation to instrumental temperature data covering the last ca. 150 years. The highest number of BRs was found in 1902, with 96% of Pinus trees and 68% of Juniperus shrubs showing BRs. These corresponded on average to a 42% vs. 27% proportion of the growth ring in 1902 which was less-lignified in Pinus trees and Juniperus shrubs, respectively. Another peak in BRs recorded for 1877 was more pronounced in Pinus trees (88%) than in Juniperus shrubs (36%), with a lower proportion of less lignified rings. We found the lowest monthly sums of growing degree days in June 1902 and August 1877, resulting in more uniform non-lignified BRs in 1902 than in 1877. Prolonged early growing season cooling shortened the growing season in 1902 and resulted in much thinner cell walls in trees and shrubs than in 1877, which was characterized by extended cooling at the end of the growing season. Also, after 1902 BR, Pinus trees exclusively showed no recovery in the mean cell wall thickness in the following year. Our study provides the first evidence for different impacts of early versus late growing season cooling on cell wall lignification in trees and shrubs at the northern treeline. Using the anatomy of BRs, we demonstrated the potential to refine summer cooling event reconstructions at an intra-annual resolution in northern Fennoscandia and beyond.